Respuesta :

STEPS USING SUBSTITUTION

5x−2y=17

2x−3y=9

 

To solve a pair of equations using substitution, first solve one of the equations for one of the variables. Then substitute the result for that variable in the other equation.

5x−2y=17,2x−3y=9

Choose one of the equations and solve it for x by isolating x on the left hand side of the equal sign.

5x−2y=17

Add 2y to both sides of the equation.

5x=2y+17

Divide both sides by 5.

x=  

5

1

(2y+17)

Multiply  

5

1

 times 2y+17.

x=  

5

2

y+  

5

17

 

Substitute  

5

2y+17

 for x in the other equation, 2x−3y=9.

2(  

5

2

y+  

5

17

)−3y=9

Multiply 2 times  

5

2y+17

.

5

4

y+  

5

34

−3y=9

Add  

5

4y

 to −3y.

−  

5

11

y+  

5

34

=9

Subtract  

5

34

 from both sides of the equation.

−  

5

11

y=  

5

11

 

Divide both sides of the equation by −  

5

11

, which is the same as multiplying both sides by the reciprocal of the fraction.

y=−1

Substitute −1 for y in x=  

5

2

y+  

5

17

. Because the resulting equation contains only one variable, you can solve for x directly.

x=  

5

2

(−1)+  

5

17

 

Multiply  

5

2

 times −1.

x=  

5

−2+17

Add  

5 /17

​ to −  

5 /2

​ by finding a common denominator and adding the numerators. Then reduce the fraction to lowest terms if possible.

x=3

The system is now solved.

x=3,y=−1